Three-dimensional incompressible flow calculations using the characteristic based split (CBS) scheme - Nithiarasu, P.; Mathur, J. S.; Weatherill, N. P.; Morgan, K. (International journal for numerical methods in fluids, 2004)
In this paper, the characteristic based split scheme is employed for the solution of three‐dimensional incompressible viscous flow problems on unstructured meshes. Many algorithm related issues are discussed. Fully explicit and semiimplicit forms of the scheme are explained and employed in the calculation of both isothermal and nonisothermal incompressible flows simulation. The extension of the scheme to porous medium flows is also demonstrated with relevant examples. Copyright © 2004 John Wiley & Sons, Ltd.